Evaluating Internal Audit, Corporate Governance, and Digital Fundraising in Improving Zakat Collection - Anam, Moh Khoirul; Yumna, Laila; Darmansyah, Dina Febriani (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2025)
This study aims to analyze management policies including internal audit development, Corporate Governance, and digital fundraising strategies and their influence on fundraising performance at Zakat institutions in Indonesia. Employing a quantitative Structural Equation Model (SEM) approach, with data analysis conducted using Smart PLS 4, data was collected via questionnaires distributed to Zakat Amil across various institutions. The results indicate that the internal audit process significantly affects Corporate Governance. Crucially, both Corporate Governance and digital fundraising were found to have a strong positive effect on Zakat fundraising outcomes. These predictor variables demonstrate very strong explanatory power, evidenced by R-squared values of 0.911 for Corporate Governance and 0.961 for Zakat collection, collectively explaining a significant portion of the variation in Zakat collection. Therefore, the main recommendation of this research is the reinforcement of internal audit as a determinant of effective governance and sustained investment in digital fundraising to maximize national Zakat potential.